Late-onset descemet membrane detachment and corneal decompensation after laser peripheral iridotomy: A case report. Issue 10 (March 2018) - Fu, Yana; Zhou, Wuying; Li, Wei; Lin, Xiaolei; Dai, Qi
Abstract: Rationale: The incidence of cornea disorders after laser peripheral iridotomy (LPI) is extremely low. However, cornea Descemet membrane detachment (DMD) combined with corneal decompensation after LPI could still occur. Patient concerns: A 69-year-old Chinese woman presented with persistent widespread corneal edema and inferior bullous lesions in her right eye for half a year. She had undergone LPI in both eyes 10 years ago for a prophylactic treatment. The patient received a detailed examination of vivo corneal confocal microscopy and sept-source optical coherence tomography (SS-OCT). Diagnoses: It was a late-onset DMD that has a positional relationship with LPI, combined with corneal decompensation. Intervention: Treatment was only supportive with artificial tears and soft contact lenses. Outcomes: This patient declined to accept keratoplasty because of financial difficulties. Lessons: Laser peripheral iridotomy may cause spontaneous, late-onset DMD and corneal decompensation. Ophthalmologists should be aware of this potential complication and proceed carefully. A careful examination of cornea especially around the LPI before keratoplasty seems to be necessary to circumvent other complication.